Criminalization Analysis Of Gambling Crime In The District Court Of The Kudus And Policies That Will Come In Penal Code Reformation - Jajang Supriyatna; Sri Endah Wahyuningish (Jurnal Daulat Hukum, 2019)
The problem in this research are: 1) Criminal prosecution against perpetrators of the Gambling Crime in the Kudus District Court. 2) Analysis of the results verdict against Gambling Crime lawsuit in the District Court of the Kudus. 3) Policy gambling a criminal offense in the Criminal Code reforms to come.Based on the results of the study concluded that: the base of the sentencing process is any act, error, and criminal prosecution. The average charges for the Gambling Crime in the District Court of the Kudus is six (6) months to 1 (one) year, but the result of a prosecution is not equal to the verdict, the general judge handed down the verdict for the Gambling Crime in the District Court of the Kudus average four (4) months to seven (7) months. Viewed from the demands of the course judges are many considerations to decide a case because the trial judges take into consideration the facts and evidence which can relieve the perpetrator gambling. That the main task of a judge is not necessarily just dropped punishment to the offender only. But also think about the consequences of sentencing, as well as considering the impact effect of what will happen later after the imposition of the witness. Creating new regulations on the prohibition of local governments to grant licenses to interested parties regarding the organization of gambling regulations, although in article 303 refer to legalize gambling if there is permission from the competent government in accordance with the PPRI No.9 of 1981. Diction abolish multiple interpretations contained in Article 303 and 303 bus or in the Bill of Article 505 where about peberian permits authorized officials in acts legalize gambling. Make one article where criminal gambling is not only subject to imprisonment and a fine of course, but also deprived of their rights in the professionalism if the perpetrator of a criminal who works with the enhancement.Keywords: Punishment; Crime Actors; Gambling; Policy; Reform.